Analisis Taman Atap Menggunakan Rain Simulator dalam Mengendalikan Limpasan Air Hujan - Kalsum, Siti Umi; Marhadi, Marhadi; Surya, Zikri Febrian (Jurnal Civronlit Unbari, 2025)
Rainfall simulator is a useful tool for controlled infiltration and runoff from open space application conditions in capturing rainwater during the rainy season. Rainfall simulators provide several benefits urban in area which can improve a quality the urban of environment, can reduce heat energy in the room, cooling process through roof closure, evapotranspiration and the heat insulator. The first factors that influence runoff consist of rain intensity and watershed characteristic factors. This research aims to determine the effect of variations in rain intensity on the resulting runoff discharge, rain erosivity index, and erosion rate using experimental methods in making a rain simulator. This study was carried out with varying slopes of 0o, 10 o, 15 o, 25 o, and 35 o with different runoff time and volume at each slope of the roof garden. Roofs that use plants on average only produce 1147.2 ml of runoff, while roofs without plants produce an average of 1492 ml of runoff with a difference of 345 ml and a percentage of 26%.